Posterior reversible encephalopathy syndrome post stem cell transplantation in sickle cell disease: case series and literature review - BinAmir, Hussain A.; AlAhmari, Ali; AlQahtani, AlWaleed; Mohamed, Gamal; Alotaibi, Fawaz; AlShamrani, Mohamed; AlSaeed, Ali; AlGhanmi, Suwaidi; Heji, Alaa; Alreshaid, Abdulrahman; AlKawi, Ammar; AlHazzani, Adel; et al. (Frontiers in Medicine, 2024)
Posterior reversible encephalopathy syndrome (PRES) is a serious neurological syndrome that may develop following immunosuppressive therapy for stem cell transplantation (SCT). We report 8 patients with sickle cell disease (SCD) who developed PRES, which is likely to be related to immunosuppression.Methods: This is retrospective cohort analysis of the SCD registry at the King Faisal Specialist Hospital and Research Center (KFSHRC) in Riyadh, Saudi Arabia. Inclusion criteria included all adults SCD patients who underwent SCT from 2011 until 2022. We explored all cases of PRES in patients with SCT. PRES was diagnosed with MRI imaging showing reversible vasogenic cerebral edema associated with neurological symptoms including severe headache, seizures, encephalopathy, delirium, and visual disturbances.Results: During ten years follow-up (2011-2022) we found 8 patients with PRES (age range between 14 to 37 years at diagnosis) PRES occurred 8 to 124 days following SCT in 7 cases and one patient developed PRES 8 months prior to SCT. All patients were on immunosuppressive medications, including tacrolimus, cyclosporine, sirolimus and or mycophenolate mofetil. Headache, seizures, visual hallucinations, confusion, and drowsiness were the most common presenting symptoms. MRI showed abnormalities in the occipital, parietal and frontal lobes in most cases. Recovery was complete in all patients and no recurrences were noted. Two patients had graft versus host disease (GVHD).We compared risk factors for PRES among the 8 cases and 136 SCT in SCD patients who did not develop PRES. There was a significant association between PRES and imaging abnormalities, including previous bi-hemispheric infarctions (P=0.001), and cerebral microbleeds (CBMs). PRES was strongly associated with presence (P=0.006), size (P=0.016) and number (P=0.005) of CMBs.Conclusions: PRES can develop days to weeks following SCT in patients with SCD, and is associated with immunosuppressive therapy, previous bi-hemispheric infarctions and CMB. Prompt recognition and intervention leads to good recovery.